Analysis of a genetic factors contributing to feathering phenotype in chickens. (19th June 2018) - Zhang, Xiuling; Wang, Han; Zhang, Lechao; Wang, Qi; Du, Xiaolong; Ge, Linhan; Zhou, Rongyan; Li, Lanhui; Li, Xianglong
Abstract: In the current study, we sought to determine whether or not the endogenous retroviral ev21 influences feathering type of chickens, and if one mutation locus in the unoccupied repeat (UR) region can be used to predict the corresponding feathering type and genotype. The distribution of ev21 as well as the mutation locus in UR and occupied site (OR) regions was detected in HY-line gray progenitor (HYGP) 4 lines, HY-line brown (HYB) and Taihang chickens (TH). Furthermore, a detection method for the genotype resulting in late feathering (LF) phenotype was developed by double PCR using C line of HYGP, C line of Dawu progenitor, commercial line of HY-line gray (HYG) males, LF males of TH and Bashang long-tail chickens (BS). Results indicated that a product of 7590 bp from the long fragment amplification was observed to be a partial segment of ev21, and was linked with the LF phenotype in HYGP but not in HYB and TH chickens. A total of 2 of 35 males and 10 of 29 females of TH LF chickens were found to be ev21 negative. Hae III RFLP mutations of 1450 bp of UR, 1440 bp of OR, and 538 bp in the UR and OR common region were analyzed, and genotypic features at the locus correlated with the feathering type phenotype in HYGP, but exhibited no significant effects in HYB and TH chickens. The cut-off of relative intensity of 857 and 1305 bp from the double PCR for distinction between homozygous and heterozygous LF males was 1.37. In conclusion, ev21 and the Hae III RFLP patterns within the locus in UR cannot be used for prediction of feathering type phenotypes in Chinese heritage chickens. However, the partial duplication of PRLR and SPEF2 were able to predict the LF phenotype. Therefore, the double PCR detecting products of 857 and 1305 bp described herein could be used for the accurate identification of genotypes influencing feathering type.